SO2 Oxidation Kinetics Leave a Consistent Isotopic Imprint on Volcanic Ice Core Sulfate. Issue 17 (4th September 2018) - Gautier, Elsa; Savarino, Joel; Erbland, Joseph; Farquhar, James
Key Points: Aerosols are physically separated from the SO2 pool during the oxidation process, and they preserve the isotopic signature during transport and deposition Volcanic sulfate of stratospheric origin scatter on Δ 33 S versus Δ 36 S and δ 34 S versus Δ 33 S slopes of −1.56 (1 σ = 0.25) and 0.09 (1 σ = 0.02), respectively The mechanism generating S‐MIF in stratospheric sulfate remains uncertain; a combination of several mechanisms is needed to reproduce the observed signature